A novel tissue‐based ß‐catenin gene and immunohistochemical analysis to exclude familial adenomatous polyposis among children with hepatoblastoma tumors. Issue 6 (15th February 2018) - Dubbink, Hendrikus J.; Hollink, Iris H.I.M.; Avenca Valente, Carolina; Wang, Wenhui; Liu, Pengyu; Doukas, Michail; van Noesel, Max M.; Dinjens, Winand N.M.; Wagner, Anja; Smits, Ron
Abstract: Background: The Wnt/β‐catenin pathway plays a central role in the pathogenesis of most hepatoblastomas (HBs), that is, up to 60–80% carry activating CTNNB1 mutations. HBs can however also be the first manifestation of familial adenomatous polyposis (FAP). As this is a severe disease, it is important for the patient and related family members to firmly exclude FAP at an early stage. Current diagnosis largely depends on APC germline mutation detection on genomic DNA, which is associated with 10–20% false‐negative results. Here, we establish and validate a tissue‐based β‐catenin gene and immunohistochemical analysis, which complements germline mutation screening to exclude the diagnosis of FAP among HB patients. Methods: Tumor tissues of 18 HB patients, including three FAP cases were subjected to CTNNB1 exon 3 mutational analysis and immunohistochemistry comparing staining patterns for total and exon 3 specific β‐catenin antibodies. Results: Our novel tissue‐based method reliably identified all three FAP patients. Their tumors were characterized by a wild‐type exon 3 sequence and a comparable nuclear staining for both antibodies. In contrast, the non‐FAP tumors carried missense CTNNB1 mutations combined with a clearly reduced staining for the exon 3 antibody, or complete loss of staining in case of lesions with exon 3 deletions. Conclusion: We have successfully established and validated a novel ß‐catenin gene and immunohistochemical diagnostic method, which, when combined with routine germline DNA testing, allows the exclusion of the diagnosis of FAP among HB patients.